2018
DOI: 10.2967/jnumed.117.207001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Bacteria in Patients Is an Attractive Fata Morgana, Not a Realistic Option

Abstract: Final results of a prospective evaluation of the predictive value of interim positron emission tomography in patients with diffuse large b-cell lymphoma treated with R-CHOP-14 (SAKK 38/07).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Over the past three decades, efforts have been made to develop single-photon emission computerized tomography (SPECT) and PET tracers that will target bacteria, and therefore, differentiate between pure inflammation and infectious disorders [ 10 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In contrast to imaging techniques such as CT and MRI, the spatial resolution of PET imaging is still suboptimal for portraying details related to targeted structures, despite significant advances that have been made in recent years.…”
Section: Limitations Of Pet For Direct Visualization Of Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past three decades, efforts have been made to develop single-photon emission computerized tomography (SPECT) and PET tracers that will target bacteria, and therefore, differentiate between pure inflammation and infectious disorders [ 10 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In contrast to imaging techniques such as CT and MRI, the spatial resolution of PET imaging is still suboptimal for portraying details related to targeted structures, despite significant advances that have been made in recent years.…”
Section: Limitations Of Pet For Direct Visualization Of Bacteriamentioning
confidence: 99%
“…In order to detect microscopic structures such as bacteria at the sites of infection, realistically, it would be necessary to accumulate a large volume in the range of 8–10 cubic mm for detection by PET imaging. Furthermore, the concentration of imaging agents by these microorganisms should be significantly higher than that of the background to reach appropriate contrast compared to surrounding background activity [ 7 , 66 , 73 , 74 , 75 , 76 ].…”
Section: Limitations Of Pet For Direct Visualization Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Spesifik bakteri görüntülemenin zorlukları vardır. Bu zorluklar bazı yayınlanmış mektup ve görüşlerle ifade edilmiş, hatta bazı yazarlar elde edilecek sonuçların bu çabaya değmeyeceğini öne sürmüşlerdir (37). Bakterilere özgü araştırmalarda farklı görüntüleme yöntemleri kullanılmaktadır (PET, SPECT ve optik görüntüleme).…”
Section: Spesifikbakteriyelgörüntülemedepotansiyel Yenigörüntülemeajaunclassified
“…Specific bacteria imaging has its challenges. These challenges have been expressed in some published letters and opinions with some even suggesting it is not worth the effort [51,52]. Studies condusted by other researchers have showed however that bacteriaspecific imaging is beneficial with some tracers being singled out as more favorable candidates [53][54][55].…”
Section: Potential New Imaging Agents To Selectively Image Bacterial mentioning
confidence: 99%